ANALYSIS OF GRAMMATICAL ERRORS IN USING SIMPLE PRESENT TENSE IN DESCRIPTIVE TEXT - Nirmala; Jamiluddin, Jamiluddin; Mashuri, Mashuri (e-Journal of ELTS (English Language Teaching Society), 2023)
This research aims to find out the kind of error frequently made by the students in using simple present tense in descriptive text and the source of errors made by the students. This research is qualitative descriptive. The subject was selected by using purposive sampling. The subject of the research was the eighth grade students of SMP Negeri 9 Palu consisting of 30 students. The techniques for collecting the data were tests and questionnaires. The researcher used the technique of analyzing the data from Ellis and Barkhuizen. The steps to analyze the data were collecting data, identification, description, explanation, and evaluation. The result indicates four types of errors namely omission, addition, misformation, and misordering. The most frequent error made by the student was omission and the least frequent error was misordering. The interlingual transfer was the highest gradation of possible source of students' error in using simple present tense.